Upaya Penguatan Pengetahuan Wali Murid Penerima Program Makan Bergizi Gratis tentang Gizi Seimbang - Juliani, Kurnia Dwi; Novianti, Anugrah (Bakti Sekawan : Jurnal Pengabdian Masyarakat, 2026)
This community engagement activity aimed to strengthen parents’ knowledge regarding balanced nutrition as part of the Free Nutritious Meal Program for school-aged children. The program was developed in response to persistent issues of low fruit and vegetable intake and unbalanced dietary patterns among students, which may hinder optimal growth and learning performance. The intervention was carried out through structured nutrition education sessions using posters and leaflets, delivered to 60 parents at SDN Cikupa 03 and SDN Cikupa 04. Activities included material presentation, interactive discussions, and pre-post evaluations to identify changes in understanding. The results showed that parents gained a clearer understanding of balanced nutrition principles, the “Isi Piringku” guide, appropriate portion sizes, and practical ways to increase children’s acceptance of fruits and vegetables. Discussions revealed strong parental interest in adopting healthier eating habits at home and overcoming challenges such as children’s preference for packaged foods and irregular eating routines. The program enhanced parents’ capacity to support healthier food environments at home, aligning school-based interventions with daily practices and reinforcing long-term behavior change. In conclusion, the activity effectively improved parental nutrition literacy and encouraged sustainable implementation of balanced nutrition for school-aged children.